THE LEVEL OF ACCORDANCE OF UNIVERSITY KNOWLEDGE TO THE REQUIREMENTS OF THE LABOUR MARKET: ANALYSIS OF THE VIEWS OF EMPLOYERS AND WAYS TO IMPROVE PUBLIC ADMINISTRATION MECHANISMS IN THE SPHERE OF ENSURING THE HIGHER EDUCATION QUALITY - Moroz, S. (Pressing Problems of Public Administration, 2020)
The problem of higher education institutions providing the quality of educational activities and the quality of higher education, including through the mechanism of improving the content and practice of educational programs’ realization, can be considered through the prism of accordance of university knowledge to the requirements of the labour market. The assessment of the level of such accordance can be made with the help of a survey of the main stakeholders of the higher education quality. Given the fact that employers are one of stakeholders of the higher education quality, their opinion regarding the level of accordance between university knowledge to the demands of the labour market, as well as improving the content and practice of using of public administration mechanisms in the sphere of ensuring of higher education quality was chosen with the author of an article as the subject of study.Clarification of the employers’ opinions was made using the tools of the survey method, namely questionnaire. Survey of employers was conducted as part of the author’s outside the grant project “Assessment of the higher education quality” The survey involved 184 employers from Kharkiv, Poltava, Sumy, as well as Ukrainian-controlled parts of Donetsk and Lugansk regions. According to the results of the analysis of the respondents’ answers, the following facts were obtained: 4% of employers believe that “the knowledge obtained during studying in the Institute of higher education almost fully does not meet the requirements of the labour market”; 38 % of employers are convinced that “the knowledge obtained during studying in the Institute of higher education most likely does not meet the requirements of the labour market”; 46 % of employers support the opinion that “the knowledge obtained during studying in the Institute of higher education generally meets the requirements of the labour market”; 8 % of employers agree with the statement that “the knowledge gained during studying in the Institute of higher education is more likely meet the requirements of the labour market”; 4 % of employers are convinced that “the knowledge gained during studying in the Institute of higher education fully complies with the requirements of the labour market” (answer options are given according to the order of their placement in the questionnaire and in compliance with the principle of their presentation from “I completely disagree with the existence of accordance between university knowledge and labour market requirements” to “I completely agree with the existence of the accordance between university knowledge and the labour market requirements”). Summarizing the opinions of respondents (abstracting from insignificant groups of respondents’ answers and grouping answers, with the direction to increase the scope of problematics consideration) letting us make a conclusion, that the number of those employers who believe that the competencies formed among students during their studying in Universities of higher education do not meet the modern requirements of the labour market in 3.5 times more than those who are convinced of the existence of such a accordance.Based on the results of the analysis of the employers’ answers, it was proposed to provide a norm for their involvement in the formation of the content of educational programs and practice of their realization, as well as in the procedures of educational programs’ accreditation. Establishing at the institutional level the norms regarding the amount of employers’ participation in the educational process and the examination procedures of educational programs, on the one hand, will lead to increase of the level of accordance between university knowledge and the labour market requirements, and on the other - will lead to increase of the educational activities quality and the higher education quality. In addition, in order to make the competencies of the graduates of Institutions of higher education closer to the needs (demands) of the labour market, it was proposed to supplement the existing system of assessment of the final knowledge of the graduates of Institutions of higher education with the obligations of the qualification exam. Employers or their representatives should become the main subjects for the knowledge assessment within the framework of such a qualification exam.